TINJAUAN PENYEDIAAN DOKUMEN REKAM MEDIS DI RSUD Dr. SOEKARDJO KOTA TASIKMALAYA - Firzah Dika Andria; Ida Sugiarti (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2015)
AbstractFast and precise services are the desire of consumers. The speed of document provision of medical records to the clinic can be an indicator in measuring satisfaction. Based on preliminary studies in dr. Soekardjo Kota Tasikmalaya found that the provision of medical record documents less than the maximum and delayed. The aim of this research is to determine the implementation of the provision of documents in the old patient medical records outpatient services. This research type is a descriptive study. Data collection used observation sheets, stopwatch, and interview guidelines. Sample size is 99 medical record documents with accidental sampling technique. The amount of sample is 99 document medical records with accidental sampling technique. Data were analyzed using univariate analysis. The results shows 63.64% late provision of medical record documents with an average time of 12.36 minutes, it exceeds the minimum standard service that is d”10 minutes. The groove of the provision of documents in the old patient medical records outpatient is 100% not appropriate. This is due to the amount of time a patient visits increased, less officer, less storage rack capacity, system alignment sequence and the absence of tracer. The conclusion is the provision of document medical record of old patients is late and the groove of the provision of documents in the old patient medical records outpatient is not appropriate. To solve those problems, it would be better if the service quality is improved, especially in the speed of medical records document provision.Keyword: speed of services, average speed, groove.AbstrakPelayanan yang cepat dan tepat merupakan keinginan konsumen. Kecepatan penyediaan dokumen rekam medis ke poliklinik dapat menjadi indikator dalam mengukur kepuasan. Berdasarkan studi pendahuluan di RSUD dr. Soekardjo Kota Tasikmalaya ditemukan bahwa dalam penyediaan dokumen rekam medis kurang maksimal dan mengalami keterlambatan. Tujuan penelitian ini adalah mengetahui pelaksanaan penyediaan dokumen rekam medis pasien lama di pelayanan rawat jalan. Jenis penelitian ini adalah penelitian deskriptif. Pengumpulan data menggunakan lembar observasi, stopwatch, dan pedoman wawancara. Besar sampel adalah 99 dokumen rekam medis dengan teknik accidental sampling. Analisis data dengan analisis univariat. Hasil penelitian menunjukan 63,64% dokumen rekam medis terlambat penyediaannya dengan rata-rata waktu 12,36 menit, melebihi standar pelayanan minimal yakni d”10 menit. Alur penyediaan dokumen rekam medis pasien lama di rawat jalan 100% tidak sesuai. Hal ini disebabkan karena jumlah kunjungan pasien lama meningkat, petugas yang kurang, kapasitas rak penyimpanan kurang, sistem penjajaran tidak berurutan dan tidak adanya tracer. Kesimpulannya penyediaan dokumen rekam medis pasien lama terlambat dan alur penyediaan dokumen rekam medis pasien lama di rawat jalan tidak sesuai. Untuk memecahkan masalah tersebut ada baiknya jika kualitas pelayanan lebih ditingkatkan khususnya dalam hal kecepatan penyediaan dokumen rekam medis.Kata Kunci: Kecepatan penyediaan, rata-rata kecepatan, alur.